Pengaruh Profitabilitas dan Leverage Terhadap Kualitas Laba dengan Kepemilikan Manajerial Sebagai Variabel Moderasi - Salsabila Tristania Agustin; Syaiful Syaiful (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This study aims to be able to test profitability and leverage on profit quality with managerial ownership as a moderation variable. This study used a sample of 78 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2022 period using the purposive sampling method. This study uses multiple linear regression analysis techniques and Moderate Regression Analysis (MRA) with IBM SPSS Statistic tools. The results of this study empirically prove that leverage affects the quality of profits. As for profitability, it has no effect on the quality of profits and managerial ownership cannot moderate the influence between profitability and leverage on the quality of profits. Further research is suggested to increase the number of company samples and extend the period of the research sample.